Analysis of marketing opportunities for the use of online channels to promote Ukrainian SMEs’ products to foreign markets - K.V.; V.V. (Економіка, управління та адміністрування)
Due to the economy digitalization and the e-commerce systems development, it is impossible to enter the foreign market without ensuring company’s presence in the global digital commercial space. Ukrainian exporters, which are trying to enter foreign markets should use multi-channel product promotion strategies including online channels. The article purpose is to study the advantages and disadvantages of using online channels for promoting products and services in foreign markets for small and medium enterprises. As a result of the study, the distinctive characteristics and features of using different online channels to promote products in foreign markets (different types of e-commerce sites, social networks and marketplaces) have been identified, as well as the advantages and disadvantages of their using for Ukrainian companies’ export activities. Also, as a result of the study, the questions for diagnostics of the company's readiness to use a multi-channel strategy for online promotion of goods in foreign markets have been formulated. It has been determined that companies that choose a multi-channel strategy and global coverage of e-commerce markets should choose international marketplaces, as they allow them to start selling globally quickly and easily. It is established that Ukrainian companies should take into account and adapt to an important trend of recent years - the intensification of M-commerce (mobile commerce). The study highlights the main most popular marketplaces in the world, which an exporter should focus on to promote products, and factors that should be considered for choosing a marketplace. This will allow exporters to make decisions for developing a marketing strategy for promoting products and services in foreign markets.